DIFFICULTIES IN TEACHING FOREIGN LANGUAGES TO YOUNG LEARNERS - Yusupova Maftuna; Jalolava M (TADQIQOTLAR, 2025)
Annotation: This article explores the various challenges educators face when teaching foreign languages to young learners. It highlights linguistic, psychological, and  pedagogical  difficulties,  such  as  short  attention  spans,  limited  first-language grammar  knowledge,  classroom  management,  maintaining  learner  motivation,  and assessing  progress.  The  article  also  discusses  the  role  of  parental  involvement  and proposes effective strategies to address these challenges.